TEORETYCZNE PRZESŁANKI UMIĘDZYNARODAWIANIA DZIAŁALNOŚCI PRZEDSIĘBIORSTWA - Kowalski, Marcin (Wydział Prawa i Administracji UAM, 2004)
The basic factor that brings about greater dynamics in economic ties on an international scale is direct foreign investments (DFI). This paper presents reasons behind the flow of capital in the form of direct foreign investment in the world economy. The review begins with the presentation of neoclassical theories, where the source of DFI is said to be the need to increase the rate of return on the capital invested which was possible due to varying levels of average return rate in different countries (theory of portfolio investment, diversification of investment portfolio theory). The author proceeds to the development of theories based on organization and behavior of the company from the standpoint of eclectic theory of international production understood a global synthesis of factors affecting the decisions on expansion of the company in the form of direct foreign investment.
THEORETICAL ASSUMPTIONS UNDERPINNING COMPANIES’ DECISIONS TO GO INTERNATIONAL